Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk dan Layanan pada Cafe Gumi Cookies - Miranda, Vudia; Sedana Yoga, I Wayan Gede; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): MaretDO - 10.24843/JRMA.2023.v11.i01.p04, 2023)
The purpose of this research is to find out the product and service attributes that are considered important by Gumi Cookies consumers, to know the product and service attributes that need priority from Gumi Cookies and to determine the level of conformity of consumer expectations and satisfaction with the quality of products and services at Gumi Cookies. The methods used in this research are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Data were obtained by distributing questionnaires to 86 respondents as a result of sampling using purposive sampling. The results showed that the attribute with the highest level of conformity in product quality was the texture of the food with a level of suitability of 101.43% and the attribute with the lowest level of conformity was the taste of the drink with a level of conformity of 89.51%. The attribute with the highest level of conformity in service quality is interior design with a level of conformity of 105.28% and the attribute with the lowest level of conformity is the cleanliness of the toilet with a level of conformity of 89.53%. very satisfied category and service quality of 85.77% with very satisfied category.